Feasibility Study. Issue 9 (September 2015) - Serrano, Geidy E.; Intorcia, Anthony; Carew, Jeremiah; Chiarolanza, Glenn; Hidalgo, Jose A.; Sue, Lucia I.; Dugger, Brittany N.; Saxon-LaBelle, Megan; Filon, Jessica; Scroggins, Alex; Pullen, Joel; Fornwalt, Brandon E.; et al.
<x xml:space="preserve">Abstract</x> Abstract The clinical diagnosis and classification of neurodegenerative diseases based on clinical examination or available biomarkers are currently insufficiently accurate. Although histologic examination is considered the gold standard for diagnosis, brain biopsies have been avoided because of the high risk-benefit ratio. However, brain biopsies have previously been performed with a craniotomy and excision of approximately 1 cm3 of cerebral cortex tissue, and it is possible that needle core brain biopsies would have a lower morbidity and mortality risk. Here, we compared the ability of simulated needle core biopsy versus simulated open biopsy to detect the frontal cortex histopathology associated with common neurodegenerative diseases in the elderly using 144 autopsy-proven cases. Simulated needle core biopsy, as compared with simulated open biopsy, gave close to 90% sensitivity and specificity for identifying graded densities of β-amyloid and neuritic plaques, neurofibrillary tangles, phosphorylated α-synuclein, and phosphorylated TDP-43 pathology. This study shows that the presence and densities of the most common molecular pathologies may be histopathologically assessed in simulated frontal cortex needle biopsies, with accuracy very close to that obtained by open cortical biopsy. An accurate estimation of the morbidity and mortality risk associated with cortical needle core biopsy will require specifically designed clinical trials in appropriate subjects.